2015
DOI: 10.1002/smll.201501026
|View full text |Cite
|
Sign up to set email alerts
|

Layer‐by‐Layer Approach to (2+1)D Photonic Crystal Superlattice with Enhanced Crystalline Integrity

Abstract: Large-area polystyrene (PS) colloidal monolayers with high mechanical strength are created by a combination of the air/water interface self-assembly and the solvent vapor annealing technique. Layer-by-layer (LBL) stacking of these colloidal monolayers leads to the formation of (2+1)D photonic crystal superlattice with enhanced crystalline integrity. By manipulating the diameter of PS spheres and the repetition period of the colloidal monolayers, flexible control in structure and stop band position of the (2+1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 60 publications
(107 reference statements)
1
37
0
Order By: Relevance
“…Particularly, polymer colloidal PCs have demonstrated important applications ranging from photonic papers [8], full-color displays [9] and UV protection [10], to responsive optic devices. Various fabrication methods for colloidal PCs have been developed to meet practical application requirements [11][12][13]. Self-assembly is a facile approach for the fabrication of colloidal PCs with stopband at UV and visible ranges [14], and could be easily modified for widespread manufacturing purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, polymer colloidal PCs have demonstrated important applications ranging from photonic papers [8], full-color displays [9] and UV protection [10], to responsive optic devices. Various fabrication methods for colloidal PCs have been developed to meet practical application requirements [11][12][13]. Self-assembly is a facile approach for the fabrication of colloidal PCs with stopband at UV and visible ranges [14], and could be easily modified for widespread manufacturing purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Gao et al reported the use of the interfacial self assembly process to cover 1 m² glass substrate with a monolayer of polystyrene spheres, highlighting the immense scalability of the process ( Figure 4) [48]. In addition, Langmuir-Blodgett and interfacial self assembly allows the possibility of stacking individual 2D layers on top of each other, thus giving the possibility to create (2 + 1)D type of colloidal crystals ( Figure 4) [41,44,47,57]. Oh et al described a simple method for fabricating wafer scale colloidal crystal film of 2D crystals in a 1D stack by combing the processes of self-assembly of polystyrene beads at the air-water interface and the layer-by-layer scooping transfer technique [47].…”
Section: Methods Remarksmentioning
confidence: 99%
“…Oh et al described a simple method for fabricating wafer scale colloidal crystal film of 2D crystals in a 1D stack by combing the processes of self-assembly of polystyrene beads at the air-water interface and the layer-by-layer scooping transfer technique [47]. Recently, Zhang et al reported the flexible control in structure and stop band position of (2 + 1)D photonic crystal superlattices by stacking of colloidal monolayers with different diameters of polystyrene ( Figure 4) [57]. arms, while at the same time monitoring the surface pressure to determine when the monolayer is closed packed.…”
Section: Methods Remarksmentioning
confidence: 99%
“…Figure 3a shows the stopband information and overlapping regions of the constituent homogeneous crystals. [27] The key stopband parameters and corresponding R AB values of the homogeneous films are shown in Table S1 (Supporting Information). The linear fitting results provided λ c = 2.528D, which was consistent with the results reported in the literature.…”
Section: Structural and Optical Features Of Mhpcsmentioning
confidence: 99%
“…The [Ru(dpp) 3 Cl 2 ] gives off the strongest FL emission at 620 nm under the excitation wavelength of 450 nm. [27] Therefore, the E and F matching MHPC was fabricated using PS spheres of 180 and 245 nm. [27] Therefore, the E and F matching MHPC was fabricated using PS spheres of 180 and 245 nm.…”
Section: Wwwadvopticalmatdementioning
confidence: 99%